Amref Health Agenda International Conference 2021_ EXECUTIVE Summary Report - Ntonjira, Elizabeth; Kimuyu, Ceciliah (Amref Health Africa)
FOREWORD: I n March, we successfully hosted the first ever virtual (and 4th in the bi-ennial series) Africa Health Agenda International Conference (AHAIC 2021). Since 2015, the Africa Health Agenda International Conference (AHAIC) has established itself as Africa’s premier forum on African health issues providing an opportunity to mobilise continental leadership, including government, civil society and the private sector, in investing in the health of the continents people. This year, the virtual conference, co-convened by the Africa CDC, Johnson and Johnson, Roche, Takeda and the International Federation of Pharmaceutical Manufacturers & Associations (IFPMA) was attended by over 3,000 delegates, from across 98 countries where the AHAIC commission for the State of UHC in Africa, established through the leadership of Amref Health Africa with support from the Bill and Melinda Gates Foundation (BMGF) released a critical report on the State of UHC in Africa. The report takes stock of the progress made by African countries toward realizing health for all through Universal Health Coverage. The Theme of the conference was Decade for Action: Driving Momentum to Achieve UHC in Africa; under the themes of Leadership, Accountability, Health, Security and Technology. The three-day conference held an array of high-level plenaries, panel discussions and town hall sessions designed to share ideas and find solutions to accelerate progress towards Universal Health Coverage (UHC) in Africa. Kenya’s President, H.E. President Uhuru Kenyatta formally opened the conference, encouraged stakeholders in health to embrace the empowerment that comes from optimism and hope even during times of uncertainty such as those caused by the COVID-19 pandemic, and urged African countries to consider seven priority areas to anchor their health policies and programmes, including giving greater priority to primary health care; increasing access to health care services; making health care more affordable; harnessing Africa’s innovative energy and creativity; strengthening health sector collaboration; improving health security and increasing political will towards UHC.
Theme: Decade for Action – Driving Momentum to Achieve UHC in Africa
Sub-themes: Leadership | Accountability | Technology | Health Security
Keywords: United Health Coverage (UHC); Health Security; Change